Epitaxial Growth of Large‐Scale Orthorhombic CsPbBr3 Perovskite Thin Films with Anisotropic Photoresponse Property. (22nd August 2019) - Wang, Yifan; Yang, Feng; Li, Xuanze; Ru, Fan; Liu, Pei; Wang, Li; Ji, Wei; Xia, Jing; Meng, Xiangmin
Abstract: Inorganic cesium lead halide perovskite (CsPbX3, X = Cl, Br, I) is a promising material for developing novel electronic and optoelectronic devices. Despite the substantial progress that has been made in the development of large perovskite single crystals, the fabrication of high‐quality 2D perovskite single‐crystal films, especially perovskite with a low symmetry, still remains a challenge. Herein, large‐scale orthorhombic CsPbBr3 single‐crystal thin films on zinc‐blende ZnSe crystals are synthesized via vapor‐phase epitaxy. Structural characterizations reveal a "CsPbBr3 (110)//ZnSe(100), CsPbBr3 [−110]//ZnSe[001] and CsPbBr3 [001]//ZnSe[010]" heteroepitaxial relationship between the covering CsPbBr3 layer and the ZnSe growth substrate. It is exciting that the epitaxial film presents an in‐plane anisotropic absorption property from 350 to 535 nm and polarization‐dependent photoluminescence. Photodetectors based on the epitaxial film exhibit a high photoresponsivity of 200 A W −1, a large on/off current ratio exceeding 10 4, a fast photoresponse time of about 20 ms, and good repeatability at room temperature. Importantly, a strong polarization‐dependent photoresponse is also found on the device fabricated using the epitaxial CsPbBr3 film, making the orthorhombic perovskite promising building blocks for optoelectronic devices featured with anisotropy. Abstract : A large‐scale orthorhombic CsPbBr3 monocrystalline thin film is synthesized on a ZnSe substrate via a resultful vapor phase epitaxial method. Due to the structural characteristic, the epitaxial film is able to exhibit an in‐plane anisotropic absorption and photoluminescence properties, making it a promising building block for polarization‐sensitive optoelectronics.